1987
DOI: 10.1111/j.1476-5381.1987.tb16821.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism between (–)‐N6‐phenylisopropyl‐adenosine and the calcium channel facilitator Bay K 8644, on guinea‐pig isolated atria

Abstract: 1 Antagonism between (-)-N6-phenylisopropyladenosine (PIA) and the dihydropyridine calcium channel facilitator Bay K 8644 was investigated in guinea-pig spontaneously beating or electrically driven isolated atria, taken from normal and from reserpine-treated animals. 2 PIA (3-100 nM) produced a dose-dependent decrease in contractile tension and frequency in spontaneously beating atria being more effective in reserpinized preparations. 3 Bay K 8644 (5-200nM) produced an increase in contractile tension in both n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…R-PIA may antagonize the positive inotropism of Ca2 + addition by directly inhibiting the Ca2+ channels. These data are in accordance with previous results showing that R-PIA and other analogues of Ado are able to antagonize the positive inotropic effect of the dihydropyridine Ca2+ L-channel activator Bay K 8644 on isolated atria (Caparrotta et al, 1987). Such effects are dependent on Al receptors and not on a direct interaction between Ado analogues and dihydropyridines at the level of specific binding sites on Ca2 + channels (Borea et al, 1989).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…R-PIA may antagonize the positive inotropism of Ca2 + addition by directly inhibiting the Ca2+ channels. These data are in accordance with previous results showing that R-PIA and other analogues of Ado are able to antagonize the positive inotropic effect of the dihydropyridine Ca2+ L-channel activator Bay K 8644 on isolated atria (Caparrotta et al, 1987). Such effects are dependent on Al receptors and not on a direct interaction between Ado analogues and dihydropyridines at the level of specific binding sites on Ca2 + channels (Borea et al, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…population of K+ channels, via guanosine 5'triphosphate (GTP)-binding proteins (Kurachi et al, 1986;Bohm et al, 1986;Cerbai et al, 1988). In previous studies (Caparrotta et al, 1987;Borea et al, 1989) we observed that in isolated atria, stable analogues of adenosine antagonized the positive inotropic effect of Bay K 8644, a dihydropyridine Ca2+ L-channel activator. Carbachol, a stable cholinoceptor agonist, was ineffective.…”
Section: Introductionmentioning
confidence: 90%
“…The sympathetic-parasympathetic interaction on the rate is greater than that on the ventricular contrac tility. The interactions between sympathomimetic sub stances and adenosine or its analogues on the atrial con tractility are also greater than that on the ventricular con tractility in the isolated mammalian hearts (12,15,30,34). These differences are partly due to the different recep tor density related to the function (35).…”
Section: Discussionmentioning
confidence: 87%
“…In the isolated, blood-per fused canine atrial preparation, we previously reported that acetylcholine and adenosine attenuated the positive chronotropic and inotropic responses to norepinephrine (14,15). These sympathoinhibitory effects of acetyl choline or adenosine on the heart are caused at sites of the intracellular signal transduction (12,13,29,30). The sympathetic-parasympathetic interactions are different among the cardiac responses, i.e., heart rate, atrioven tricular conduction, atrial contractility, ventricular con tractility and refractory period, in the dog heart (14, 31 33).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, it is interesting to stress that a marked cross tachyphylaxis between milrinone and the Ca ' § activator, Bay K 8644, has been observed in dog and guinea-pig cardiac tissue and that both drugs interact with adenosine binding sites [5,36,37]. Moreover, nanomolar concentrations of the stable adenosine derivative, (-)-N%phenyliso-propyladenosine, were sho~ to antagonize the inotropie effect of Bay K 8644 in an apparently competitive manner [38]. These data suggest that Ca'~+-channel activation by milrinone [39] can be strictly related to its antagonistic effect at adenosine Pl receptors and suggest the possibility of inducing inotropic responses without increasing the cAMP level, thus avoiding the related risk of harmful arrhythmias [40].…”
Section: Discussionmentioning
confidence: 96%